Health Risks and Roles in Medical Surveillance among Nurses Working in BPO Sectors in Iloilo City, Philippines - Melveen Melocoton (Eurasian Journal of Science and Engineering)
The increasing globalization of business processes has led to the expansion of business process outsourcing (BPO) sectors, particularly in countries like the Philippines. Nurses, a significant group in the workforce in these sectors, are tasked with providing medical and health-related services. However, nurses in the BPO sector face health risks such as occupational hazards, ambiguous OSH regulations and procedures, and limited OSH knowledge and engagement in medical surveillance. This descriptive-comparative research investigated nurses’ health risks and roles in medical surveillance in the BPO sectors of Iloilo City, Philippines. A total of 49 nurses from 69 BPO firms in Iloilo City were the study's respondents. According to BPO firm profiles, there were significant differences between nurses' health risks and roles in medical surveillance. To prevent health risks and improve the roles in medical surveillance among nurses in the BPO sector, management must actively develop, innovate, and evaluate their occupational safety and health (OSH) policies and programs, as well as empower their nurses through professional development and training.